Extended 3He-rich Time Periods Observed by Solar Orbiter: Magnetic Connectivity and Sources - A. Kouloumvakos; G. M. Mason; G. C. Ho; R. C. Allen; Robert F. Wimmer-Schweingruber; A. P. Rouillard; J. Rodriguez-Pacheco (The Astrophysical Journal, 2023)
Observations of Solar Energetic Particles (SEPs) using the Suprathermal Ion Spectrograph (SIS), which is part of the Energetic Particle Detector suite on the Solar Orbiter mission, present an unprecedented opportunity to investigate the composition and evolution of SEPs in close proximity to the Sun. By analyzing data from the SIS instrument, we have compiled a catalog of extended time periods during the first five orbits of the spacecraft around the Sun, which exhibit a significant abundance of ^3 He. We have identified 33 periods lasting over one day that show a high abundance of ^3 He. For each period, we examined the SEP characteristics, the magnetic connectivity of the spacecraft, and the magnetically connected regions. Our findings show that these time periods typically span seven days and consist of multiple injections of ^3 He, and that the peak in ^3 He flux is observed two days after the time periods begin. The time periods usually start (end) when the spacecraft’s magnetic connection changes to (from) an active region (AR). In most cases, we observed a stable magnetic connection between the spacecraft and one or more ARs, with an average connection time of 4.1 ± 1.8 days.